2021
DOI: 10.30787/gaster.v19i1.658
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Body Mass Index (BMI) and Sex in Adolescent Training Resistance

Abstract: Adolescents 18-21 years of age today have problems related to movement that result in changes to resistance training. Exercise resistance is expressed in VO2max. Body mass index and gender are factors that influence VO2max. The purpose of this study is to analyze the relationship between body mass index and sex on VO2Max and to analyze how closely the relationship is. The type of this study is an observational study with a purposive sampling technique with a point time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…This is contrary to a recent research study [ 46 ] which revealed that six weeks of circuit training significantly increased the predicted VO 2 max of adolescents who participated in the intervention programme. Contrary to previous research studies [ 47 , 48 , 49 ], gender and age did not produce any significant influence on the VO 2 max of the treatment group. Therefore, future research should consider larger sample sizes, longer intervention durations, and control for additional confounding variables to better understand the determinants of VO 2 max changes in adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…This is contrary to a recent research study [ 46 ] which revealed that six weeks of circuit training significantly increased the predicted VO 2 max of adolescents who participated in the intervention programme. Contrary to previous research studies [ 47 , 48 , 49 ], gender and age did not produce any significant influence on the VO 2 max of the treatment group. Therefore, future research should consider larger sample sizes, longer intervention durations, and control for additional confounding variables to better understand the determinants of VO 2 max changes in adolescents.…”
Section: Discussioncontrasting
confidence: 99%
“…There are several sex-specific factors that influence VO 2 max, such as the timing of puberty, body composition, and growth patterns. Previous observational studies in children and adolescents have reported higher VO 2 max in boys than in girls [ 26 , 27 , 28 ]. In addition, many studies have indicated that height and weight are significant predictors of VO 2 max [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%